Symptomatic treatment in patients with multiple sclerosis [Multipl sklerozlu hastalarda semptomatik tedavi] - (:unkn) unknown (My University, 2004)
Although the absolute number is not known, it is estimated that 30-35 thousand people suffer from multiple sclerosis (MS) in Turkey. MS is classified according to its clinical status. In most of the patients, it occurs as inflammation and neurological insufficiency attacks followed by remissions. During the advanced acute stage, acute attacks either lessen or completely disappear. Treatment strategies for MS are categorized in five groups: treatment of the attacks, management of the symptoms, patient adaptation, rehabilitation and psychological support. Although the symptoms of MS are classified as primary, secondary and tertiary, they are generally seen together. The complications of this disorder, for which a definitive treatment has not yet been found, may be bettered only if an adequate care is provided and an effective symptom management is ensured through patient and family education, and thus the quality and period of life may be enhanced. Therefore, the patient assessment should cover all dimensions, including the symptoms that are directly related to the disorder, as well as complications related with the symptoms. The problems that MS patients most frequently experience and strategies to manage these problems are presented in this article.